Voltage- and time-dependent valence state transition in cobalt oxide catalysts during the oxygen evolution reaction - Jing Zhou (Nature Portfolio, 2020)
Determining catalyst electronic structures during electrochemical reactions is crucial to understand mechanisms. Here authors perform in operando soft X-ray spectroscopy on a cobalt oxide catalyst during O2 evolution and observe voltage and time-dependent valence state transitions.